"A plantation can be a commons": Re‐Earthing Sapelo Island through Abolition Ecology: The 2018 Neil Smith Lecture. Issue 1 (25th May 2020) - Heynen, Nik
Abstract: This paper is based on the 2018 Neil Smith Lecture presented at the University of St Andrews. It considers the plantation past/futures of Sapelo Island, Georgia, one of the Sea Islands forming an archipelago along the US Southeastern coast. I work through the abolitionist efforts of the Saltwater Geechee's who have resided there since at least 1803 to better understand how we can mobilise an emancipatory politics of land and property and to produce commons that work to repair and heal the violence done through enslavement and ongoing displacement. I weave together a series of historical threads to better situate linked ideas of abolition democracy and abolition geography, and to extend the notion of abolition ecology as a strategic notion to connect Eurocentric based political ecologies with the emancipatory tradition of Black geographies.